Exploring Omani EFL Learners’ Perceptions of AI Tools - Ali, Eassa; Pushpavilasam Veettil, Roy; Al‑Zaabi, Mohammed Ali; Sharafudeen, Misaj; Qureshi, Tanveer (Digital Technologies Research and Applications, 2025)
This study employed the Technology Acceptance Model to investigate Omani English as a foreign language (EFL) learners’ perceptions and use of ChatGPT in English learning settings. A predominantly quantitative descriptive design was adopted, using a questionnaire that included primarily closed‑ended items with three open‑ended items added to support the quantitative findings. The data were collected from 198 students of two higher education institutions in Oman. Quantitative findings revealed that Omani EFL learners used ChatGPT both inside and outside class for learning English, mainly for obtaining explanations for unclear concepts and ideas, obtaining answers for English exercises, grammar correction and support, and idea generation. The correlation analysis shows that more frequent and longer use of ChatGPT was associated with a wider range of English learning purposes. The learners reported strong ease of use, positive attitudes towards ChatGPT, and an intention to pursue using it. The qualitative findings supported the quantitative results, emphasizing that ChatGPT improved learners’performance in terms of grammar, writing fluency, vocabulary building, confidence and learning autonomy. However, the qualitative findings revealed some concerns about overreliance, accuracy, limited contextual depth, and academic integrity. Both sets of findings suggest that while Omani EFL learners are ready to adopt and integrate ChatGPT into EFL learning, they are cautious about the unguided use of it. Future research may extend this work to examine the long‑term impact of ChatGPT on EFL learners across a wider range of higher education institutions within and beyond the Sultanate of Oman.